Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Section: 1 v. (xi-276 p.) ; 23 cm
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

J'aime à toi : esquisse d'une félicité dans l'histoire - Irigaray, Luce (Grasset, 1992)
Qui es-tu, toi qui n'es, ne seras jamais moi ni mien ? Je t'écoute comme la révélation d'une vérité irréductible à moi. Tu m'as saluée, reconnue. Tu interroges tes limites. Je te donne du silence où le futur de toi - et peut-être de moi avec toi - peut émerger et se fonder. Je ne m'approche pas immédiatement de toi. Je ne te connaîtrai jamais de manière absolue. Je laisse de l'air, de l'espace, du mystère autour de nous. Éveillée à toi, recueillie, j'invente des paroles qui te touchent de leur souffle sans t'enlever à toi. Cet abord intransitif cherche aide auprès de l'univers, de la beauté, de la sagesse, de l'Histoire. En cette uvre déjà, j'aime à toi. Puisse ce " à " garder l'intention entre nous encore et toujours vive, berceau de l'être que notre transcendance l'un à l'autre enfante. " Après une critique de la maîtrise de notre culture par le genre masculin et la définition de médiations nécessaires à la constitution du sujet féminin, Luce Irigaray élabore ici une dialectique de l'intersubjectivité fondée sur la différence sexuelle. J'aime à toi marque donc un nouveau temps dans l'ouvre de la philosophe, le premier ayant été ouvert par Speculum, De l'autre femme.
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

La nature humaine est deux - Irigaray, Luce (J'aime à toi : esquisse d'une félicité dans l'histoire, 1992)
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Gender and knowledge: Elements of a postmodern feminism - Hekman, Susan J. (Northeastern University Press, 1990)
The aim of the book is to explore the connection between two perspectives that have had a profound effect upon contemporary thought: post-modernism and feminism. Through bringing together and systematically analysing the relations between these, Hekman is able to make a major intervention into current debates in social theory and philosophy. The critique of Enlightenment knowledge, she argues, is at the core of both post-modernism and feminism. Each also offers a basis for critical reflections about the other. In particular, post-modern philosophy provides a means of criticizing aspects of contemporary feminism and thus contributing to the development of a more sophisticated approach to current feminist issues.
Keywords: 1700-1799; 1900-1999; 1980-1989; approches et analyses; cours; discipline; europe; fem1000; france; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; études culturelles

Feminism/postmodernism - Nicholson, Linda J. (Routledge, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis